Penerapan Teknik Modeling untuk Meningkatkan Kedisiplinan Anak Usia Dini di Taman Kanak-kanak - Asri, Nur; Siswono, Hendrik; Sugiarto, Muhammad Agus (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The research background relates to the application of modeling techniques to improve the disciplinary character of early childhood children at Kartini II Kindergarten PGRI Rambipuji Jember. This is based on the results of observations before the research, the level of discipline of group A students has not developed well. Some disciplinary characteristics that have not developed well include throwing trash in the right place and entering class on time, so efforts are needed to encourage the development of children's disciplinary character to improve well. One learning model that can be used to develop students' disciplined character is modeling techniques. The aim of the research is how the application of modeling techniques can improve the disciplined character of children in group A TK Kartini II PGRI Rambipuji Jember.Method – This research is classroom action research, with the research instrument in the form of an observation sheet with 3 observed indicators related to students' disciplinary character. Analysis of research data uses percentage techniques, with the criterion of individual student completeness getting a minimum of 3 stars on each indicator observed. As for the classical completion criteria, if 80 percent of students complete each indicator observed.Findings – The results of classroom action research regarding the application of modeling techniques in improving the disciplinary character of class A students, it can be concluded that the criteria for research completeness can be achieved. The details of the research results in the pre-cycle completeness reached 37 percent, in the first cycle activities it reached 56 percent, and in the second cycle the level of completeness reached 87 percent. Research Implications – Based on the findings from two cycles of classroom action research, the use of modeling techniques can effectively enhance the discipline character of class A students at Kartini II.